2020
DOI: 10.34117/bjdv6n6-602
|View full text |Cite
|
Sign up to set email alerts
|

Metodologia alternativa para o teste de germinação em sementes de soja tratada

Abstract: RESUMOO tratamento de sementes é amplamente utilizado para proteger as sementes das culturas frente a ação de insetos e patógenos,entretanto, alguns pesticidas podem causar fitotoxicidade àsplântulas durante o teste de germinação. Assim, o objetivo deste trabalho foi avaliar diferentes substratos e metodologias alternativas para o teste de germinação em sementes tratadas de soja. As sementes foram submetidas a três tratamentos químicos (Cruiser ® 350 FS; Maxim XL e Avicta Completo), conforme as doses recomenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…Regarding the substrate used, Pereira et al (2000) found that, in general, germination in sand was superior to the results obtained for paper rolls, when evaluating different cultivars and sowing dates. It is presumed that, depending of the seed treatment, the quality of seeds germinated in paper can be hindered compared to those germinated in sand, due to the presence of an aggravating factor for such an event, as observed in this study, which leads to the observation by some authors, that the substrate most suitable for the germination test depends on the type of product and active ingredient in seed treatment (Tunes et al, 2020). Unlike sand, on paper the active ingredient remains concentrated around the seeds, which can lead to the known phytotoxic effect.…”
Section: Resultsmentioning
confidence: 65%
“…Regarding the substrate used, Pereira et al (2000) found that, in general, germination in sand was superior to the results obtained for paper rolls, when evaluating different cultivars and sowing dates. It is presumed that, depending of the seed treatment, the quality of seeds germinated in paper can be hindered compared to those germinated in sand, due to the presence of an aggravating factor for such an event, as observed in this study, which leads to the observation by some authors, that the substrate most suitable for the germination test depends on the type of product and active ingredient in seed treatment (Tunes et al, 2020). Unlike sand, on paper the active ingredient remains concentrated around the seeds, which can lead to the known phytotoxic effect.…”
Section: Resultsmentioning
confidence: 65%
“…It was verified a reduction of 93% (2 min), 85% (4 min), and 100% (10 min) in germination compared to seeds without residue in this same neutralizer. The toxicity during germination has been reported in soybean seeds due to chemical treatments; the concentration of these products in contact with the seed is 3.500 times more compared to the emergence in soil (Tunes et al, 2020). Although the neutralizer residue significantly affected germination, its removal proved to be beneficial, resulting in germination rates of approximately 80% across all delinting times.…”
Section: Resultsmentioning
confidence: 99%
“…Tal dosagem se enquadra dentro do recomendado na bula do produto a qual recomenda uma dosagem de 300 mL.100 -1 kg de sementes a 600 mL.100 -1 kg de sementes. Fonte: Dados da pesquisa (2022). Palavras-chave: MDF, Sustentabilidade, Meio ambiente, Marcenaria, Impacto Ambiental.…”
Section: Resultados E Discussõesunclassified
“…constatado porTunes et al, (2020), que realizaram teste de germinação com 25 e 50 sementes de soja por germitest. Os autores constataram que o teste de germinação com sementes sem adição de produto químico com o germitest o resultado não diferiu quanto a quantidade de sementes utilizadas.Conforme está estabelecido nas Regras para análise de sementes (RAS), o teste de germinação possui como principal objetivo determinar o máximo potencial de germinação de um determinado lote de sementes, e assim, consegue-se entender a viabilidade do lote, sendo que este é o momento ao qual consegue-se verificar se a plântula possui todas as estruturas essências para o estabelecimento de uma planta normal.…”
unclassified